Konflik Batin Tokoh Utama dalam Novel Air Mata Surga Karya E. Rokajat Asura: Tinjauan Psikologi Sastra dan Implementasinya dalam Pembelajaran Sastra di SMK - Nugroho, Ganang Galih Prasetyo, Dr. Nafron Hasjim (2017)
Abstract This study attempts to build (1) described structure in a novel Air Mata Surga by E. Rokajat Asura, (2) described inner conflict with review the main character psychology literature in a novel Air Mata Surga by E. Rokajat Asura, (3) and described the findings novel Air Mata Surga will work E. Rokajat Asura as material literature in SMK. This research is descriptive qualitative.The research is inner conflict the main character in a novel Air Mata Surga. Engineering collecting data which used in this research was, library a look at, note, and interview. The validity of data techniques used in this research is a technique trianggulasi data. Technique analysis the data used in this research with a model analysis interactive. Based on the results of the analysis is can be concluded as follows. (1) Structural analysis produce the (a) theme this novel is the story of suffering live a little girl. (b) The main figure is Baraah and additional is, baraah's mother, baraah's father, baraah's aunt, baraah's uncle, mrs fatema, uztadzah salma, doctor mohammed, and hasina. (c) A groove used is the backwards ( flashback). (d) Background divided into three parts: background place in the district of sayyedah Zainab, mecca apartment, madrasah ibtidaiyah andalus, mahmudiyya cairo and hospitals sharm el-shikh, ; background when there was 6 months; and social background narrating the lives society middle-class. (2) Conflict inner the main figure in a novel Air Mata Surga work by E. Rokajat Asura, among them were mendekat-menjauh (approach-avoidance conflict) and conflict menjauh-menjauh ( avoidance-avoidance conflict ). (3) the result of this research implemented as teaching materials literature in SMK based on 2013 curriculum kd 3.9 analyze the content and kebahasaan with subject matter element intrinsic and extrinsic novel.